Spatiotemporal molecular tracing of ultralow-volume biofluids via a soft skin-adaptive optical monolithic patch sensor - Yeon Soo Lee; Seyoung Shin; Gyun Ro Kang; Siyeon Lee; Da Wan Kim; Seongcheol Park; Youngwook Cho; Dohyun Lim; Seung Hwan Jeon; Soo-Yeon Cho; Changhyun Pang (Nature Communications)
Abstract Molecular tracing of extremely low amounts of biofluids is vital for precise diagnostic analysis. Although optical nanosensors for real-time spatiotemporal molecular tracing exist, integrating them into simple devices that capture low-volume fluids on rough, dynamic surfaces remains challenging. We present a bioinspired 3D microstructured patch monolithically integrated with optical nanosensors (3D MIN) for real-time, multivariate molecular tracing of ultralow-volume fluids. Inspired by tree frog toe pads, the 3D MIN features soft, hexagonally aligned pillars and microchannels for conformal adhesion and targeted fluid management. Embedding near-infrared fluorescent single-walled carbon nanotube nanosensors in a hydrogel enables simultaneous fluid capture and detection. Softening the elastomer microarchitecture and optimizing water management promote stable adhesion on wet biosurfaces, allowing rapid collection of ultralow-volume fluids (~0.1 µL/min·cm²). We demonstrate real-time, remote sweat analysis with ≥75 nL volumes collected in 45 s, without exercise or iontophoresis, showcasing high biocompatibility and efficient spatiotemporal molecular tracing.